Main Areas of Human Development I: Emotional, Cognitive, and Social Growth From Birth to Late Adolescence - Barta, Andrea (Social and Personality Development in Childhood, 2025)
This chapter provides an overview of human development, specifically focusing on the characteristics of cognitive, emotional, and social development from birth to late adolescence, through an overview of major foundational psychological theories. The goal of this chapter is to offer a comprehensive understanding of the diversity and relevance of emotional, cognitive, and social processes by presenting different, complementary theoretical approaches, illustrated with practical, real-life examples.Despite presenting aspects of emotional, cognitive, and social development separately within the chapter, numerous theories and approaches, as well as research evidence, are presented that emphasise the interconnected and reciprocal nature of these processes. Proper functioning of the cognitive system is necessary for the establishment of balanced emotional states and social relationships because, as detailed within the chapter, according to certain cognitive emotion theories, emotions arise based on the cognitive evaluation of external events and internal states. Similarly, a lot of empirical evidence demonstrates that the social environment plays a primary role in a child’s appropriate emotional, cognitive, and psychosocial development.The chapter also highlights the first two years of life as a critical period in not only cognitive and emotional but also social development. Experiences acquired during this period influence later developmental stages. Positive experiences and a supportive social environment lead to the development of adaptive cognitive schemas that contribute to later balanced social and emotional development. In contrast, negative experiences and an unsupportive social environment can result in the formation of schemas that increase the likelihood of difficulties in emotional and social development; unsuccessful resolution of age-specific crises; and likelihood of the emergence of psychopathologies such as anxiety, depression, and personality disorders. Keywords: cognitive development, emotional development, social development, sociocultural context, learning